Wpływ wybranych czynników społeczno-demograficznych i medycznych na akceptację choroby w grupie osób z cukrzycą typu 2 = The influence of selected socio-demographic and medical factors on the acceptance of illness in a group of patients with type 2 diabetes mellitus - Cecylia Olszak; Elżbieta Nowicka; Bożena Baczewska; Robert Łuczyk; Beata Kropornicka; Ewa Krzyżanowska; Jadwiga Daniluk (Kazimierz Wielki University, 2016)
Olszak Cecylia, Nowicka Elżbieta, Baczewska Bożena, Łuczyk Robert, Kropornicka Beata, Krzyżanowska Ewa, Daniluk Jadwiga. Wpływ wybranych czynników społeczno-demograficznych i medycznych na akceptację choroby w grupie osób z cukrzycą typu 2 = The influence of selected socio-demographic and medical factors on the acceptance of illness in a group of patients with type 2 diabetes mellitus. Journal of Education, Health and Sport. 2016;6(12):11-28. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192107 http://ojs.ukw.edu.pl/index.php/johs/article/view/4028       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 01.12.2016.       Wpływ wybranych czynników społeczno-demograficznych i medycznych na akceptację choroby w grupie osób z cukrzycą typu 2 The influence of selected socio-demographic and medical factors on the acceptance of illness in a group of patients with type 2 diabetes mellitus   Cecylia Olszak1, Elżbieta Nowicka1, Bożena Baczewska1, Robert Łuczyk1, Beata Kropornicka1, Ewa Krzyżanowska1, Jadwiga Daniluk1   1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie       Słowa kluczowe: akceptacja choroby, cukrzyca typu 2, czynniki społeczno-demograficzne, czynniki medyczne   Key words: acceptance of illness, type 2 diabetes mellitus, socio-demographic factors, medical factors   Streszczenie   Wstęp. Identyfikacja barier utrudniających przystosowanie się do cukrzycy stanowi ważną część opieki diabetologicznej. Akceptację cukrzycy znacząco warunkują czynniki  emocjonalne, społeczne, ekonomiczne  i kliniczne. Celem badania było określenie stopnia akceptacji choroby wśród pacjentów  z cukrzycą  typu 2  w zależności od wybranych zmiennych społeczno-demograficznych i medycznych. Materiał i metoda. Badaniem objęto 227 pacjentów z cukrzycą typu 2 hospitalizowanych w Klinice Endokrynologii i leczonych w Poradni Diabetologicznej w SPSK4 w Lublinie. Zastosowano Skalę Akceptacji Choroby (AIS) oraz autorski kwestionariusz ankiety. Wyniki badań. Płeć, miejsce zamieszkania, stan cywilny, BMI,  HbA1c  nie różnicowały statystycznie istotnie (p>0,05) wyników AIS. Wykazano różnicę statystycznie istotną (p<0,01) między wiekiem ankietowanych a wynikiem średniej  na skali AIS. Stwierdzono różnicę statystycznie istotną (p<0,01) pomiędzy wynikiem AIS  a aktywnością zawodową respondentów. Zaobserwowano różnicę statystycznie istotną (p<0,05) w zakresie zapotrzebowania na wsparcie duchowe i emocjonalne a wynikami AIS. Uzyskano statystycznie istotną różnicę (p<0,05) pomiędzy wynikiem akceptacji choroby a czasem trwania choroby. Stwierdzono różnicę statystycznie istotną (p<0,05) pomiędzy metodą leczenia oraz udziałem w szkoleniach a skalą AIS.  Występowała różnica istotna statystycznie (p<0,05) pomiędzy wynikiem średniej skali AIS i udziałem w szkoleniach na temat cukrzycy. Wnioski. 1. Osoby chorujące na cukrzycę typu 2 w większości wykazywały przeciętny poziom akceptacji choroby. 2. Obniżenie poziomu akceptacji choroby związane było z zaawansowanym wiekiem, dłuższym czasem trwania choroby, udziałem w szkoleniach oraz z  zapotrzebowaniem na wsparcie emocjonalne i duchowe. 3. Na wzrost akceptacji choroby miały wpływ czynna praca zawodowa oraz leczenie cukrzycy doustnymi lekami  hipoglikemizującymi.           Abstract   Introduction. The identification of barriers that hinder the adaptation to diabetes constitutes an important part of diabetes care. The acceptance of diabetes is considerably dependent on emotional, social, economic and clinical factors. The aim of the study was to assess the level of acceptance of illness in patients with type 2 diabetes mellitus in relation to selected socio-demographic and medical variables. Material and method. The study included 227 patients with type 2 diabetes mellitus who were treated at the Clinic of Endocrinology and Diabetes Outpatient Clinic of the Independent Public Clinical Hospital No 4 in Lublin. The Acceptance of Illness Scale (AIS) was applied along with the authors' questionnaire specially compiled for the study.  The results. Gender, place of residence, marital status BMI, HbA1c did not diversify the AIS scores statistically significantly (p>0,05). There was a statistically significant difference (p<0,01) between the participants' age and the average score of the AIS. A statistically significant difference (p<0,01) was also noticed between the AIS result and the respondents' professional activity. The relation between the requirement for both spiritual and emotional support and the AIS result was statistically significant (p<0,05). The difference between  disease acceptance and duration of illness was found to be statistically significant (p<0,05). The relationship between the AIS result and the treatment method along with participation in trainings on diabetes was statistically significant (p<0,05). The was a statistically significant difference (p<0,05) between the mean score of the AIS and participation in trainings on diabetes. Conclusions. 1. The patients suffering from type 2 diabetes mellitus mainly showed the average disease acceptance. 2. The lower level of acceptance of illness was connected with advanced age, longer duration of the disease, participation in trainings and need for emotional and spiritual support. 3. The increase in acceptance of illness was affected by active working life and diabetes treatment with oral hypoglycemic drugs.